Proactive Agents to Assist Multimodal Explorative Learning of Astronomical Phenomena. (14th December 2008) - Tuominen, Eva; Kangassalo, Marjatta; Hietala, Pentti; Raisamo, Roope; Peltola, Kari
Abstract : This paper focuses on developing, testing, and examining the Proagents multimodal learning environment to support blind children's explorative learning in the area of astronomy. We utilize haptic, auditive, and visual interaction. Haptic and auditory feedbacks make the system accessible to blind children. The system is used as an exploration tool for children's spontaneous and question-driven explorations. High-level interaction and play are essential with environments for young children. Proactive agents support and guide children to deepen their explorations and discover the central concepts and relations in phenomena. It has been challenging to integrate together in a pedagogically relevant way the explorative learning approach, proactive agents' actions, haptic perception's possibilities, and the selected astronomical phenomena. Our tests have shown that children are very interested in using the system and the operations of the agents.